A Foucauldian Approach in Stephen King’s The Green Mile - Kadhim Hussein, Nada (Opción, 2019)
This study aims to analyze The Green Mile by Stephen King in the light of the foucauldian approach of power in modern institutions. Discipline and Punish:The Birth of the Prison (Foucault, 1995) contributes to better under- standing of the unusual role of prison literature in tackling such sharp issues as power structures and dynamics in modern prison systems. The study be- gins with detailed discussion of some theorists’ ideas about institutional power. Then, it ends with analysis of the relations between prison conditions and rac- ism in the novel. As the focus of this study is relationship between the prison system and the institutionalized racism in the United States as reflected in The Green Mile, the analysis demonstrates the complex interplay between control and opposition and the strategies of power and resistance that are commonly exercised with prisons by prison writers when defending their ideas, values, principles, and freedom against a dominant oppressing power.